Flexible piezoresistive sensor, intelligent glove and unmanned aerial vehicle gesture control method
Through the combination of flexible piezoresistive sensors and smart gloves, the gesture signal is converted into drone control signals using high-sensitivity pressure detection technology, solving the problem that existing drone control methods cannot be sensitive and precisely controlled, and achieving high efficiency , accurate drone control.
Patent Information
- Application Number
- CN202411518320.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Existing UAV control methods cannot control UAVs sensitively and accurately, especially in long-distance or complex environments, making it difficult to achieve precise operation.
Using flexible piezoresistive sensors and smart gloves, the microcracks of multi-wall carbon nanotube film are combined with the laminated structure of microconical polydimethylsiloxane film layer, composite film layer and polydimethylsiloxane film layer. The structure realizes high-sensitivity pressure detection, and converts gesture signals into drone control signals through microcontrollers and wireless communication modules.
It realizes precise control of drones, improves operational sensitivity and response speed, is suitable for drone control in various environments, and lowers the technical threshold for operators.
Smart Images

Figure CN119469488A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of unmanned aerial vehicle control, and in particular to a flexible piezoresistive sensor, a smart glove and a method for controlling unmanned aerial vehicle gestures. Background Art
[0002] Consumer drones require simple and convenient operation, and the market demand for consumer drones is increasing. However, most drones still rely on remote controls or smart device applications for operation, which are complex and inconvenient to control, and require high professionalism from the operator. For the general public, there is a certain learning cost, which is not conducive to the popularization of drones.
[0003] Although gesture control has appeared in drone control, most of them use pattern recognition or image recognition gestures. Image recognition requires camera modules, sensors and image processing chips with a certain degree of clarity, which is costly. At long distances, the accuracy of image recognition gestures is not high, which can easily lead to misoperation. In emergency situations or complex environments (such as dark light, foggy weather, etc.), it is difficult to respond to the operator's instructions quickly or accurately, which has great limitations and cannot perfectly meet the needs of drone control.
[0004] Existing drone controls mainly use pattern recognition or image recognition gestures. The sensors used have poor recognition effects at long distances or in complex environments, making it difficult to control the drone sensitively and accurately. Therefore, existing drone control methods are unable to control the drone sensitively and accurately, and have great limitations. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a flexible piezoresistive sensor, smart gloves and a drone gesture control method, aiming to solve the problem that the control methods of drones in the prior art cannot control drones sensitively and accurately and have great limitations.
[0006] In order to solve the above technical problems, the purpose of the present invention is achieved through the following technical solutions:
[0007] On the one hand, the present invention discloses a flexible piezoresistive sensor, comprising a micro-conical polydimethylsiloxane film layer, a composite film layer and a polydimethylsiloxane film layer stacked in sequence from bottom to top; wherein the composite film layer comprises a thermoplastic polyurethane elastomer fiber film and a micro-crack multi-walled carbon nanotube film, the thermoplastic polyurethane elastomer fiber film is bonded to the micro-conical polydimethylsiloxane film layer, the micro-crack multi-walled carbon nanotube film is bonded to the polydimethylsiloxane film layer; conductive electrode materials are attached to both ends of the micro-crack multi-walled carbon nanotube film; the micro-crack multi-walled carbon nanotube film The thickness of the film is 1-10 μm; the preparation steps of the composite film layer include: coating an aqueous dispersion of multi-walled carbon nanotubes on a thermoplastic polyurethane elastomer fiber film, drying it, and then stretching and rebounding it to obtain the composite film layer with a micro-crack multi-walled carbon nanotube film; the preparation steps of the micro-conical polydimethylsiloxane film layer include: evenly mixing a polydimethylsiloxane matrix and a curing agent, pouring it into a mold with a micro-conical structure, curing it, and then taking it out to obtain the micro-conical polydimethylsiloxane film layer; the thickness of the micro-conical polydimethylsiloxane film layer is 0.2-1 mm.
[0008] Optionally, the thickness ratio of the micro-conical polydimethylsiloxane film layer, the micro-crack multi-walled carbon nanotube film, the thermoplastic polyurethane elastomer fiber film and the polydimethylsiloxane film layer is: (200-1000): (1-10): (50-200): (200-1000).
[0009] Optionally, the preparation steps of the thermoplastic polyurethane elastomer fiber membrane include: dissolving a thermoplastic polyurethane elastomer in an organic mixed solvent to obtain a thermoplastic polyurethane elastomer solution, and electrospinning the thermoplastic polyurethane elastomer solution to obtain the thermoplastic polyurethane elastomer fiber membrane; the organic mixed solution is selected from at least one of a mixture of dimethylformamide and ethyl acetate and a mixture of dimethylformamide and tetrahydrofuran; in the thermoplastic polyurethane elastomer solution, the mass fraction of the thermoplastic polyurethane elastomer is 18-25wt%; the parameters of the electrospinning treatment are: voltage 14-16kV, distance between needle and collector 12-18cm, flow rate of the thermoplastic polyurethane elastomer solution is 1-4mL / h.
[0010] Optionally, in the preparation step of the composite film layer, the aqueous dispersion of the multi-walled carbon nanotubes contains multi-walled carbon nanotubes and a dispersant, the mass fraction of the multi-walled carbon nanotubes is 8-12wt%, and the mass fraction of the dispersant is 1-4wt%; the diameter of the multi-walled carbon nanotubes is 10-25nm, and the length is 5-15μm; the crack spacing of the micro-crack multi-walled carbon nanotube film is 80-120μm.
[0011] Optionally, in the step of preparing the micro-conical polydimethylsiloxane film layer, the mass ratio of the polydimethylsiloxane matrix to the curing agent is (8-12):1.
[0012] Optionally, the flexible piezoresistive sensor also includes a first polyurethane film layer and a second polyurethane film layer, the first polyurethane film layer is arranged below the micro-conical polydimethylsiloxane film layer, and the second polyurethane film layer is arranged above the polydimethylsiloxane film layer; the thickness of the first polyurethane film layer is 50-150μm, and the thickness of the second polyurethane film layer is 50-150μm.
[0013] On the other hand, the present invention discloses a smart glove, comprising a glove body and the flexible piezoresistive sensor as described above; the flexible piezoresistive sensor is attached to the glove body.
[0014] Optionally, the smart glove further comprises a main control board, which comprises a fixed resistor, a single chip microcomputer, a filter, an operational amplifier and a wireless communication module; the number of the flexible piezoresistive sensors is four, which are respectively attached to the glove body at the positions of the fingertips of the fingers of the human body except the thumb, and are used to identify and collect finger pressure signals; the single chip microcomputer is connected to the wireless communication module;
[0015] The flexible piezoresistive sensor has a resistor; each of the flexible piezoresistive sensors is connected in series with the fixed resistor to form a voltage divider circuit, converting the change in resistance value into a voltage divider change, which then passes through the filter and the operational amplifier in sequence to form a stable voltage signal, which is input into the single-chip microcomputer.
[0016] In addition, the present invention also discloses a drone gesture control method, comprising the following steps:
[0017] Step 1: Put on the smart gloves on your hands and install the drone command execution module on the drone body;
[0018] The smart gloves are the smart gloves described above;
[0019] The drone command execution module includes a flight control module and a Raspberry Pi;
[0020] The Raspberry Pi receives the command signal and converts the command signal into a control signal corresponding to the flight mode of the drone; at the same time, the Raspberry Pi is connected to the flight control module, and the flight control module controls the drone body to complete various actions;
[0021] Step 2: determining whether the flexible piezoresistive sensor is in a hard pressing state or a light pinching state by setting a threshold;
[0022] Step 3: Input the state information combination of the flexible piezoresistive sensor into the single chip microcomputer to obtain the gesture state corresponding to each combination of information and the instruction corresponding to the gesture state;
[0023] Step 4: The executor performs corresponding gestures with fingers as required, and the single chip microcomputer transmits the command signal to the Raspberry Pi through the wireless communication module;
[0024] Step 5: After receiving the command signal, the Raspberry Pi converts the gesture into a drone control signal, thereby controlling the drone to complete the command action.
[0025] Optionally, the gesture state in step three and the instruction corresponding to the gesture state include:
[0026] The thumb gently pinches the index finger, and the drone performs a descent operation;
[0027] Press the thumb hard on the index finger, and the drone will land.
[0028] Squeeze the middle finger with your thumb, and the drone will move forward.
[0029] Press the middle finger with your thumb to make the drone move backwards.
[0030] Slightly pinch the ring finger with the thumb, and the drone will fly to the left;
[0031] Press the ring finger hard with the thumb, and the drone will fly to the right;
[0032] Squeeze the little finger with your thumb, and the drone will ascend.
[0033] Press the little finger hard with the thumb, and the drone will take off;
[0034] The light pinching pressure is 5-30 kPa, and the heavy pressing pressure is 80-200 kPa.
[0035] Beneficial effects:
[0036] In the flexible piezoresistive sensor, smart gloves and drone gesture control method of the present invention, the flexible piezoresistive sensor includes a micro-conical polydimethylsiloxane film layer, a composite film layer and a polydimethylsiloxane film layer. The micro-crack multi-walled carbon nanotube film of the composite film layer has micron-level cracks, which expand under the action of physical pressure, and can increase the number of resistance paths inside the film, thereby causing a significant decrease in resistance; and the micron-level cracks enable the micro-crack multi-walled carbon nanotube film to produce obvious electrical signal changes under the action of tiny forces, greatly improving the sensitivity and operational response speed of the sensor; the micro-conical polydimethylsiloxane film layer has a micro-conical structure, which can increase the specific surface area of the film by increasing the density and distribution uniformity of the micro-conical structure, thereby improving the sensitivity of the film, thereby more accurately capturing and transmitting tiny pressure changes.
[0037] Therefore, the flexible piezoresistive sensor can quickly change its resistance value when subjected to force, thereby achieving fast response and high-sensitivity pressure detection. It has high sensitivity and accuracy, can accurately capture and transmit tiny pressure changes, and can be applied to smart gloves that use drone gesture control methods. It can sensitively sense the pressure changes caused by gesture changes, thereby accurately controlling the drone. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.
[0039] Figure 1 is a cross-sectional view of the flexible piezoresistive sensor of the present invention;
[0040] Figure 2 is a schematic diagram of a flexible piezoresistive sensor of the present invention;
[0041] Figure 3 This is a finished product picture of the flexible piezoresistive sensor prepared in Example 1 of the present invention;
[0042] Figure 4 This is a schematic diagram of the cyclic electrical signal response of the flexible piezoresistive sensor prepared in Example 1 of the present invention under different pressing degrees;
[0043] Figure 5 It is a stress cloud diagram comparison diagram of the micro-cone PDMS film layer prepared in Example 1 of the present invention, the micro-pyramid PDMS film layer prepared in Comparative Example 2, the micro-cylindrical PDMS film layer prepared in Comparative Example 3, and the micro-prismatic PDMS film layer prepared in Comparative Example 4 under different strains;
[0044] Figure 6It is a strain-pressure test data comparison diagram of the micro-cone PDMS film layer prepared in Example 1 of the present invention, the micro-pyramid PDMS film layer prepared in Comparative Example 2, the micro-column PDMS film layer prepared in Comparative Example 3, and the micro-prismatic PDMS film layer prepared in Comparative Example 4;
[0045] Figure 7 This is a finished product picture of the smart gloves made in Example 1 of the present invention;
[0046] Figure 8 This is a circuit diagram of the main control board of the smart glove made in Example 1 of the present invention;
[0047] Fig. 9 Schematic diagram of the drone gesture control method of the present invention.
[0048] Description of reference numerals:
[0049] 1. Composite film layer; 11. TPU fiber film; 12. Microcrack MWCNTs film; 2. Microconical PDMS film layer; 3. PDMS film layer; 4. Electrode material; 5. Second PU film layer; 6. First PU film layer; V in , power supply voltage; R s , resistance of flexible piezoresistive sensor; R1, fixed resistor; C1, filter; T1, operational amplifier; D1, microcontroller. DETAILED DESCRIPTION
[0050] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.
[0052] A flexible piezoresistive sensor comprises a micro-cone polydimethylsiloxane film layer (i.e., a micro-cone PDMS film layer), a composite film layer and a polydimethylsiloxane film layer (i.e., a PDMS film layer) stacked in sequence from bottom to top. The composite film layer comprises a thermoplastic polyurethane elastomer fiber film (i.e., a TPU fiber film) and a micro-crack multi-walled carbon nanotube film (i.e., a micro-crack MWCNTs film); the thermoplastic polyurethane elastomer fiber film is bonded to the micro-cone polydimethylsiloxane film layer, and the micro-crack multi-walled carbon nanotube film is bonded to the polydimethylsiloxane film layer.
[0053] The thickness of each membrane layer directly affects the microstructural morphology of the flexible piezoresistive sensor. In the present application, the thickness of the microcrack MWCNTs membrane of the composite membrane layer is preferably 1-10μm, specifically 1μm, 2μm, 4μm, 8μm, 10μm; the thickness of the TPU fiber membrane is preferably 50-200μm, specifically 50μm, 100μm, 120μm, 140μm, 200μm. At the same time, the thickness of the micro-cone PDMS film layer is preferably 0.2-1mm, specifically 0.2mm, 0.5mm, 0.8mm, 1.0mm; wherein the diameter of the micro-cone is 100-150um, and the height is 80-120um; the thickness ratio of the micro-cone PDMS film layer, the micro-crack MWCNTs film, the TPU fiber film and the PDMS film layer is preferably any value within (200-1000): (1-10): (50-200): (200-1000), specifically 200: 1: 50: 200, 500: 4: 100: 500, 1000: 10: 200: 1000, 600: 6: 200: 400, 800: 10: 120: 600, 400: 8: 140: 600.
[0054] The microcrack structure of the microcracked MWCNTs film expands under the action of physical pressure, which can increase the number of resistance paths inside the film, thereby causing a significant decrease in resistance; and the micron-sized cracks enable the microcracked MWCNTs film to produce obvious electrical signal changes under the action of tiny forces, greatly improving the sensitivity and operational response speed of the sensor; the thickness of the microcracked MWCNTs film can affect the number of resistance paths inside the film, thereby affecting its sensitivity and operational response speed under stress conditions.
[0055] The preparation steps of the composite film layer include: coating a multi-walled carbon nanotube aqueous dispersion on a TPU fiber film, drying, and then stretching and rebounding to obtain a composite film layer with a microcracked MWCNTs film. That is, the composite film layer uses the TPU fiber film as a substrate and obtains a microcracked MWCNTs film on the surface.
[0056] The preparation steps of the TPU fiber membrane include: dissolving a thermoplastic polyurethane elastomer in an organic mixed solvent to obtain a thermoplastic polyurethane elastomer solution, and performing electrospinning on the thermoplastic polyurethane elastomer solution to obtain the TPU fiber membrane.
[0057] The organic mixed solution is selected from at least one of a mixture of dimethylformamide and ethyl acetate and a mixture of dimethylformamide and tetrahydrofuran; preferably, in the mixture of dimethylformamide and ethyl acetate, the mass ratio of the two is (1-4):1, specifically 1:1, 2:1, 3:1, 4:1; the mass ratio of the mixture of dimethylformamide and tetrahydrofuran is (0.5-2):1, specifically 0.5:1, 1:1, 2:1.
[0058] In the thermoplastic polyurethane elastomer solution, the mass fraction of the thermoplastic polyurethane elastomer is preferably 18-25wt%.
[0059] The parameters of the electrospinning treatment are preferably: voltage 14-16kV, distance between needle and collector 12-18cm, flow rate of the thermoplastic polyurethane elastomer solution 1-4mL / h. The parameters of the electrospinning treatment can interact with each other to affect the formation structure of the fiber membrane. When the voltage is too high, the jet will be unstable, resulting in a wider fiber diameter distribution; when the voltage is too low, it is difficult to overcome the surface tension of the solution, resulting in a larger fiber diameter and difficulty in forming continuous fibers; if the needle is too close to the collector, the jet will not be fully dried and stretched; if the needle is too far from the collector, the fiber yield will be reduced and the cost will be increased; if the flow rate is too fast, the solvent will not be fully volatilized, causing the fiber diameter to increase and form a bead defect; if the flow rate is too slow, the jet will be unstable and the ideal fiber structure cannot be obtained.
[0060] The diameter, length, mass fraction of multi-walled carbon nanotubes and the mass fraction of dispersant can all affect the crack structure of the obtained film layer. The aqueous dispersion of multi-walled carbon nanotubes contains multi-walled carbon nanotubes and dispersants. The mass fraction of the multi-walled carbon nanotubes is preferably 8-12wt%, and the mass fraction of the dispersant is preferably 1-4wt%; the diameter of the multi-walled carbon nanotubes is preferably 10-25nm, and the length is preferably 5-15μm; it can ensure that the surface of the obtained film has a micron-level crack structure; prevent the multi-walled carbon nanotubes from being unevenly dispersed, and excessive agglomeration leads to uneven film structure and difficulty in forming cracks; it can also prevent the multi-walled carbon nanotubes from being too dispersed, resulting in decreased mechanical properties and difficulty in rebounding after stretching. The crack spacing of the microcrack MWCNTs film is preferably 80-120μm. The dispersant is preferably a polymer dispersant, which can be polyvinyl pyrrolidone, polyvinyl pyrrolidone, sodium polyacrylate, etc.
[0061] The aqueous dispersion of multi-walled carbon nanotubes is coated on the TPU fiber film, and the coating rate is preferably 2-5 mm / s. Too fast or too slow coating rate will lead to uneven coating. The thermoplastic polyurethane elastomer fiber film coated with the aqueous dispersion of multi-walled carbon nanotubes is dried under the conditions of temperature 25-30°C, humidity 40-50%, and drying in a well-ventilated environment; too high humidity will affect the drying effect, making it difficult to completely dry, prolonging the production cycle, or making the crack structure unclear after stretching; too low humidity is prone to over-drying, causing the film to become hard and brittle, making it difficult to perform subsequent stretching operations.
[0062] Conductive electrode materials are provided at both ends of the microcrack MWCNTs membrane; the conductive electrode materials can be attached before or after stretching, and the conductive electrode materials are used for connection and conduction. The conductive electrode materials can be selected from flexible conductive materials, such as elastic silver paste, nickel-copper conductive fabric, silver fiber fabric, electrode materials containing carbon-based conductive additives, copper foil, etc.
[0063] The purpose of the stretching operation is to destroy the surface structure of the film layer and form a crack structure on its surface; the stretching rate is preferably 1-4mm / s, and the film layer is stretched to 100% strain and then released. The surface area of the film layer changes very little after rebound, but a micron-level crack structure can be formed; the stretching is bidirectional stretching, that is, simultaneous stretching in the transverse and longitudinal directions; the stretching strength and rate should be moderate to prevent unnecessary damage to the film layer.
[0064] The preparation steps of the micro-cone PDMS film layer include: uniformly mixing a polydimethylsiloxane matrix and a curing agent, pouring the mixture into a mold with a micro-cone structure, curing the mold, and then taking out the micro-cone PDMS film layer to obtain the micro-cone PDMS film layer.
[0065] The micro-cone PDMS membrane layer can increase the specific surface area of the membrane by increasing the density and distribution uniformity of the micro-cone structure, thereby improving the sensitivity of the membrane and capturing and transmitting tiny pressure changes more accurately.
[0066] Wherein, the mass ratio of the polydimethylsiloxane matrix to the curing agent is (8-12): 1; the toughness and elasticity of the film layer are increased. The curing agent can be the corresponding curing agent, which can be selected from hydrogen silicone oil, monobutyl phthalate, special curing agent C-100, etc.; preferably, a two-component product of Sylgard 184 can be selected, Sylgard 184 includes a matrix and a curing agent, wherein the curing agent is vinyl-terminated polydimethylsiloxane (Vinyl-Terminated PDMS). The mold with a micro-cone structure can be a bionic structure mold. More specifically, the mold with a micro-cone structure can be selected from a mold obtained by rubbing and molding paper mulberry leaves. The template with a micro-cone structure can reduce the cost by rubbing and molding the leaves, and the paper mulberry leaves also have a micro-cone structure, which can be used as a mold to prepare a micro-cone PDMS film layer. The curing parameters are preferably cured for 1-4 hours in a vacuum environment at 40-80°C and 0.5-2bar.
[0067] The mold with a micro-cone structure can be obtained by mixing PDMS (i.e., polydimethylsiloxane) and a curing agent evenly, pouring it over the blade, curing it, and demolding it; in the mold with a micro-cone structure, the mass ratio of PDMS to the curing agent is preferably 3-6:1, so that it has a stronger hardness; and the curing agent can be selected from hydrogen silicone oil, monobutyl phthalate, special curing agent C-100, etc.; the curing parameters are preferably 40-80°C, 0.5-2bar in a vacuum environment for 3-6h. In the mold with a micro-cone structure, in order to avoid the formation of an overly strong chemical bond between the mold and the subsequent coating, a layer of metal nanoparticle film is sprayed on the surface of the mold using a magnetron sputtering device, and the metal nanoparticles can be platinum nanoparticles, gold nanoparticles, etc.
[0068] The preparation method of the flexible piezoresistive sensor is to stack the micro-cone PDMS film layer, the composite film layer and the PDMS film layer from bottom to top, and then encapsulate them with a polyurethane film layer; that is, the flexible piezoresistive sensor preferably also includes a first polyurethane film layer (i.e., the first PU film layer) and a second polyurethane film layer (i.e., the second PU film layer), the first PU film layer is arranged below the micro-cone PDMS film layer, and the second PU film layer is arranged above the PDMS film layer; the thickness of the first PU film layer is 50-150 μm, and the thickness of the second PU film layer is 50-150 μm. Both the first PU film layer and the second PU film layer are preferably PU films with high elasticity and medical grade.
[0069] The PDMS membrane layer can be an existing commercially available product, or can be obtained by uniformly mixing a polydimethylsiloxane matrix with a curing agent and curing the mixture.
[0070] Reference Figure 1 and Figure 2The flexible piezoresistive sensor can be composed of a micro-conical PDMS film layer 2, a composite film layer 1 and a PDMS film layer 3 stacked from bottom to top; the composite film layer 1 includes a TPU fiber film 11 and a micro-crack MWCNTs film 12, and electrode materials 4 are attached to both ends of the micro-crack MWCNTs film 12; specifically, the electrode material 4 is located between the micro-crack MWCNTs film 12 and the PDMS film layer 3, which can prevent the PDMS film layer 3 from destroying the carbon nanotube structure in the micro-crack MWCNTs film 12 to a certain extent.
[0071] At the same time, the first PU film layer 6 is attached to the bottom of the micro-cone PDMS film layer 2, and the second PU film layer 5 is attached to the top of the PDMS film layer 3, for packaging and protecting the internal laminated structure.
[0072] The prepared flexible piezoresistive sensor can be used to monitor the pressure range of 0-200 kPa, and can show good sensitivity under low, medium and high pressures. Specifically, the flexible piezoresistive sensor can show -0.14004 kPa in the low, medium and high pressure ranges respectively. -1 、-0.00268kPa -1 and -0.00149 kPa -1 sensitivity.
[0073] In Example 1, a flexible piezoresistive sensor is prepared by the following steps.
[0074] (1) Preparation of TPU fiber membrane
[0075] TPU particles (WHT-1180; TPU thermoplastic elastomer; specific gravity: 1.18 g / cm 3 ) was dried in a vacuum oven at 80°C for 24 hours to remove moisture. Subsequently, the TPU particles were dissolved in a mixed solvent of dimethylformamide (DMF) and ethyl acetate (EAC) at a concentration of 20wt%, with a volume ratio of DMF to EAC of 2:1. The dissolution process was carried out at 80°C and magnetic stirring was performed for 8 hours to ensure that the particles were completely dissolved to obtain a TPU solution.
[0076] Next, using an electrospinning device, the prepared TPU solution was placed in a 10mL syringe equipped with a 20-gauge blunt needle, and the flow of the solution was precisely controlled by a digital syringe pump. The electrospinning process was carried out at room temperature and 60% humidity, with a voltage of 15kV applied, the distance between the needle and the collector maintained at 15cm, the drum speed of the collector set to 100rpm, and the flow rate of the solution was 2mL / h. Under the action of the electric field, the solvent evaporated rapidly to form a continuous TPU fiber membrane, which was finally vacuum dried at room temperature for 12 hours to remove the residual solvent to obtain a TPU fiber membrane.
[0077] (2) Preparation of composite film layer
[0078] A heated flat plate coater was used to evenly coat 0.5 mL of a multi-walled carbon nanotube aqueous dispersion on the TPU fiber membrane at a speed of 5 mm / s, wherein the multi-walled carbon nanotubes had an average tube diameter of 15 nm, an average length of 10 μm, and a solid content of 10 wt %; and the dispersant was polyvinyl pyrrolidone with a content of 2 wt %.
[0079] The TPU fiber membrane was cut into 30mm×100mm size in advance. After coating, the membrane was fixed on a flat surface and dried for 3 hours in a low humidity 45% and well-ventilated room temperature environment. The dried membrane was further cut into 30mm×30mm segments and copper foil was attached to both ends as electrode materials.
[0080] Next, these membranes were mounted on a tensile testing machine and subjected to biaxial stretching in the longitudinal and transverse directions at a stretching rate of 2 mm / s. After being stretched to 100% strain, they were released and stretched once. Through biaxial stretching, a micro-cracked MWCNTs membrane with a micron-scale crack structure was formed on the surface of the membrane, thereby obtaining a composite membrane layer. The thickness of the micro-cracked MWCNTs membrane was 5 μm, and the average crack spacing was 100 μm.
[0081] (3) Preparation of micro-conical PDMS film layer
[0082] First, fresh paper mulberry leaves were selected as templates with microcone structures. The leaves were thoroughly cleaned with deionized water, air-dried at room temperature for 20-30 minutes, cut into 25mm×25mm segments, and fixed to the bottom of the mold with UV glue. Next, Sylgard184 (Sylgard184 is a two-component product including a matrix and a curing agent) was mixed and degassed at a mass ratio of 5:1 between the matrix and the curing agent and poured on top of the leaves with a thickness of greater than or equal to 3mm, and cured for 4 hours in a vacuum environment at 65°C and 0.9bar. After curing, the PDMS negative mold was carefully removed and ultrasonically cleaned with 70% ethanol to remove the residual leaf material. In order to avoid the formation of too strong a chemical bond between the PDMS negative mold and the subsequent coating, a thin gold film was sprayed on the surface of the negative mold using a magnetron sputtering device for 120 seconds. The prepared PDMS negative mold was used as a mold with a microcone structure in the future. In the PDMS negative mold, the average diameter of the microcones was 120um and the height was 100um.
[0083] Subsequently, PDMS mixed with Sylgard184 in a mass ratio of matrix to curing agent of 10:1 was poured into the PDMS negative mold and cured again in a vacuum environment of 65°C and 0.9 bar for 2 hours, finally obtaining a micro-conical PDMS film layer imitating the micro-conical structure of paper mulberry leaves.
[0084] (4) Assembling the flexible piezoresistive sensor
[0085] The micro-cone PDMS film layer, the composite film layer and the PDMS film layer are stacked in sequence from bottom to top; then the stacked film layers are wrapped in the middle with a PU film, that is, the bottom of the micro-cone PDMS film layer is in close contact with the first PU film layer, and the top of the PDMS film layer is in close contact with the second PU film layer.
[0086] The PDMS film layer is obtained by uniformly mixing Sylgard 184 with a base and a curing agent in a mass ratio of 10:1, and curing the mixture in a vacuum environment at 65° C. and 0.9 bar for 2 hours.
[0087] The side of the micro-cone PDMS membrane layer having the bionic micro-cone structure is in contact with the TPU fiber membrane.
[0088] The thickness of the micro-cone PDMS film layer is 0.5 mm, the thickness of the TPU fiber film is 150 μm, the thickness of the micro-crack MWCNTs film is 5 μm, and the thickness of the PDMS film layer is 0.5 mm. The first PU film layer is the same as the second PU film layer, both are medical grade PU films, and the thickness is 0.1 mm.
[0089] In Example 2, a flexible piezoresistive sensor is prepared by the following steps.
[0090] (1) Preparation of TPU fiber membrane
[0091] TPU particles (WHT-1180; TPU thermoplastic elastomer; specific gravity: 1.18 g / cm 3 ) was dried in a vacuum oven at 80°C for 24 hours to remove moisture therein. Subsequently, the TPU particles were dissolved in a mixed solvent of DMF and tetrahydrofuran (THF) at a concentration of 20wt%, with a volume ratio of DMF to THF of 1:1. The dissolution process was carried out at 80°C and magnetic stirring was performed for 8 hours to ensure that the particles were completely dissolved to obtain a TPU solution.
[0092] Next, using an electrospinning device, the prepared TPU solution was placed in a 10mL syringe equipped with a 20-gauge blunt needle, and the flow of the solution was precisely controlled by a digital syringe pump. The electrospinning process was carried out at room temperature and 60% humidity, with a voltage of 14kV applied, the distance between the needle and the collector maintained at 12cm, the drum speed of the collector set to 100rpm, and the flow rate of the solution was 1mL / h. Under the action of the electric field, the solvent evaporated rapidly to form a continuous TPU fiber membrane, which was finally vacuum dried at room temperature for 12 hours to remove the residual solvent to obtain a TPU fiber membrane.
[0093] (2) Preparation of composite film layer
[0094] A heated flat plate coater was used to evenly coat 0.1 mL of a multi-walled carbon nanotube aqueous dispersion on the TPU fiber membrane at a speed of 5 mm / s, wherein the multi-walled carbon nanotubes had an average tube diameter of 10 nm, an average length of 15 μm, and a solid content of 8 wt %; and the dispersant was polyvinyl pyrrolidone, with a content of 1.8 wt %.
[0095] The TPU fiber membrane was cut into 30mm×100mm size in advance. After coating, the membrane was fixed on a flat surface and dried for 3 hours in a low humidity 45% and well-ventilated room temperature environment. The dried membrane was further cut into 30mm×30mm segments and copper foil was attached to both ends as electrode materials.
[0096] Next, these membranes were mounted on a tensile testing machine and subjected to biaxial stretching in the longitudinal and transverse directions at a stretching rate of 1.5 mm / s. After being stretched to 100% strain, they were released and stretched once. Through biaxial stretching, a micro-cracked MWCNTs membrane with a micron-scale crack structure was formed on the surface of the membrane, thereby obtaining a composite membrane layer. The thickness of the micro-cracked MWCNTs membrane was 1 μm, and the average crack spacing was 84 μm.
[0097] (3) Preparation of micro-conical PDMS film layer
[0098] First, fresh paper mulberry leaves were selected as templates with microcone structures. The leaves were thoroughly cleaned with deionized water, air-dried at room temperature for 20-30 minutes, cut into 25mm×25mm segments, and fixed to the bottom of the mold with UV glue. Then, Sylgard184 was mixed and degassed in a mass ratio of 5:1 between the matrix and the curing agent and poured on top of the leaves with a thickness of 3mm or more, and cured in a vacuum environment of 65℃ and 0.9bar for 4 hours. After curing, the PDMS negative mold was carefully removed and ultrasonically cleaned with 70% ethanol to remove the residual leaf material. In order to avoid the formation of too strong chemical bonds between the PDMS negative mold and the subsequent coating, a thin gold film was sprayed on the surface of the negative mold with a magnetron sputtering device for 120 seconds. The prepared PDMS negative mold was used as a mold with a microcone structure in the future. In the PDMS negative mold, the average diameter of the microcones was 100um and the height was 80um.
[0099] Subsequently, PDMS mixed with Sylgard184 in a specific mass ratio of 8:1 with the curing agent was poured into the PDMS negative mold, and cured again in a vacuum environment at 65°C and 0.9 bar for 1.5 hours, finally obtaining a micro-conical PDMS film layer imitating the micro-conical structure of paper mulberry leaves.
[0100] (4) Assembling the flexible piezoresistive sensor
[0101] The micro-cone PDMS film layer, the composite film layer and the PDMS film layer are stacked in sequence from bottom to top; then the stacked film layers are wrapped in the middle with a PU film, that is, the bottom of the micro-cone PDMS film layer is in close contact with the first PU film layer, and the top of the PDMS film layer is in close contact with the second PU film layer.
[0102] The PDMS film layer is obtained by uniformly mixing Sylgard 184 with a base and a curing agent in a mass ratio of 10:1, and curing the mixture in a vacuum environment at 65° C. and 0.9 bar for 2 hours.
[0103] The side of the micro-cone PDMS membrane layer having the bionic micro-cone structure is in contact with the TPU fiber membrane.
[0104] The thickness of the micro-cone PDMS film layer is 0.2 mm, the thickness of the TPU fiber film is 100 μm, the thickness of the micro-crack MWCNTs film is 1 μm, and the thickness of the PDMS film layer is 0.2 mm. The first PU film layer is the same as the second PU film layer, both are medical grade PU films, and the thickness is 0.05 mm.
[0105] In Example 3, a flexible piezoresistive sensor is prepared by the following steps.
[0106] (1) Preparation of TPU fiber membrane
[0107] TPU particles (WHT-1180; TPU thermoplastic elastomer; specific gravity: 1.18 g / cm 3 ) was dried in a vacuum oven at 80°C for 24 hours to remove moisture therein. Subsequently, the TPU particles were dissolved in a mixed solvent of DMF and EAC at a concentration of 20wt%, with a volume ratio of DMF to EAC of 3:1. The dissolution process was carried out at 80°C and magnetic stirring was performed for 8 hours to ensure that the particles were completely dissolved to obtain a TPU solution.
[0108] Next, using an electrospinning device, the prepared TPU solution was placed in a 10mL syringe equipped with a 20-gauge blunt needle, and the flow of the solution was precisely controlled by a digital syringe pump. The electrospinning process was carried out at room temperature and 60% humidity, with a voltage of 16kV applied, the distance between the needle and the collector maintained at 18cm, the drum speed of the collector was set to 100rpm, and the flow rate of the solution was 3mL / h. Under the action of the electric field, the solvent evaporated rapidly to form a continuous TPU fiber membrane, which was finally vacuum dried at room temperature for 12 hours to remove the residual solvent to obtain a TPU fiber membrane.
[0109] (2) Preparation of composite film layer
[0110] The TPU fiber membrane was prepared by the same preparation process as the TPU fiber membrane, and 0.8 mL of multi-walled carbon nanotube aqueous dispersion was evenly coated on the TPU fiber membrane at a speed of 5 mm / s using a heated flat coater, wherein the average tube diameter of the multi-walled carbon nanotubes was 25 nm, the average length was 5 μm, and the solid content was 12 wt%; the dispersant was polyvinyl pyrrolidone, and the content was 2.2 wt%.
[0111] The TPU fiber membrane was cut into 30mm×100mm size in advance. After coating, the membrane was fixed on a flat surface and dried for 3 hours in a low humidity 45% and well-ventilated room temperature environment. The dried membrane was further cut into 30mm×30mm segments and copper foil was attached to both ends as electrode materials.
[0112] Next, these membranes were mounted on a tensile testing machine and subjected to biaxial stretching in the longitudinal and transverse directions at a stretching rate of 2.5 mm / s. After being stretched to 100% strain, they were released and stretched once. Through biaxial stretching, a micro-cracked MWCNTs membrane with a micron-scale crack structure was formed on the surface of the membrane, thereby obtaining a composite membrane layer. The thickness of the micro-cracked MWCNTs membrane was 8 μm, and the average crack spacing was 112 μm.
[0113] (3) Preparation of micro-conical PDMS film layer
[0114] First, fresh paper mulberry leaves were selected as templates with microcone structures. The leaves were thoroughly cleaned with deionized water, air-dried at room temperature for 20-30 minutes, cut into 25mm×25mm segments, and fixed to the bottom of the mold with UV glue. Then, Sylgard184 was mixed and degassed in a mass ratio of 5:1 between the matrix and the curing agent and poured on top of the leaves with a thickness of 3mm or more, and cured in a vacuum environment of 65℃ and 0.9bar for 4 hours. After curing, the PDMS negative mold was carefully removed and ultrasonically cleaned with 70% ethanol to remove the residual leaf material. In order to avoid the formation of too strong chemical bonds between the PDMS negative mold and the subsequent coating, a thin gold film was sprayed on the surface of the negative mold with a magnetron sputtering device for 120 seconds. The prepared PDMS negative mold was used as a mold with a microcone structure in the future. In the PDMS negative mold, the average diameter of the microcones was 150um and the height was 120um.
[0115] Subsequently, PDMS mixed with Sylgard184 in a mass ratio of matrix to curing agent of 12:1 was poured into the PDMS negative mold and cured again in a vacuum environment of 65°C and 0.9 bar for 3 hours, finally obtaining a micro-conical PDMS film layer imitating the micro-conical structure of paper mulberry leaves.
[0116] (4) Assembling the flexible piezoresistive sensor
[0117] The micro-cone PDMS film layer, the composite film layer and the PDMS film layer are stacked in sequence from bottom to top; then the stacked film layers are wrapped in the middle with a PU film, that is, the bottom of the micro-cone PDMS film layer is in close contact with the first PU film layer, and the top of the PDMS film layer is in close contact with the second PU film layer.
[0118] The PDMS film layer is obtained by uniformly mixing Sylgard 184 with a base and a curing agent in a mass ratio of 10:1, and curing the mixture in a vacuum environment at 65° C. and 0.9 bar for 2 hours.
[0119] The side of the micro-cone PDMS membrane layer having the bionic micro-cone structure is in contact with the TPU fiber membrane.
[0120] The thickness of the micro-cone PDMS film layer is 1 mm, the thickness of the TPU fiber film is 200 μm, the thickness of the micro-crack MWCNTs film is 10 μm, and the thickness of the PDMS film layer is 1 mm. The first PU film layer is the same as the second PU film layer, both are medical grade PU films, and the thickness is 0.15 mm.
[0121] Meanwhile, the following comparative examples 1-9 are set according to Example 1, and the differences between comparative examples 1-9 and Example 1 are shown in the following table. Comparative examples 1-9 are prepared by the same method as Example 1 to obtain flexible piezoresistive sensors.
[0122] Table 1 Differences between Example 1 and Comparative Examples 1-9
[0123]
[0124]
[0125] Among them, the flexible piezoresistive sensor prepared in comparative example 1 has a short service life, mainly because the micro-cone structure directly contacts the micro-cracked MWCNTs film, which is not conducive to the service life of the sensor. Specifically, although the surface energy of PDMS is extremely low, some carbon nanotubes will still adhere to it during use, causing the carbon nanotube film to be damaged; the PDMS with a micro-cone structure has more destructive structural characteristics and a larger contact surface area than the unstructured PDMS layer, which will damage the carbon nanotube layer to a greater extent, resulting in unstable electrical signal response of the sensor under long-term use, and reduced sensor service life.
[0126] The micro-cone PDMS film layer prepared in Example 1, the micro-pyramid PDMS film layer prepared in Comparative Example 2, the micro-column PDMS film layer prepared in Comparative Example 3, and the micro-prismatic PDMS film layer prepared in Comparative Example 4 were subjected to strain tests.
[0127] The strain test conditions are as follows: the finite element method (FEM) was used to simulate the mechanical response under compression, and the stress distribution and strain behavior of the microstructure on PDMS were evaluated using the general simulation software COMSOL Multiphysics. The simulation was based on an accurate PDMS hyperelastic compression model using the Mooney-Rivlin 5-parameter model (material parameters: C01 = 114.08 [kPa], C02 = -269.88 [kPa], C10 = 145.06 [kPa], C11 = 450.72 [kPa], C20 = 156.23 [kPa]).
[0128] Attached Figure 5 In the figure, from left to right, the strain test results of the micro-cone PDMS film layer prepared in Example 1, the micro-pyramid PDMS film layer prepared in Comparative Example 2, the micro-column PDMS film layer prepared in Comparative Example 3, and the micro-prismatic PDMS film layer prepared in Comparative Example 4 are shown respectively; Figure 5 and attached Figure 6 It can be seen that the micro-cone PDMS film layer prepared in Example 1 has stronger pressure sensitivity.
[0129] The flexible piezoresistive sensors prepared in Examples 1-3 and Comparative Examples 5-9 were tested.
[0130] Test equipment: pressure tester / vibrator, multimeter / impedance analyzer, data acquisition system Test environment: room temperature
[0131] Test method: 1. Fix the flexible sensor on the workbench of the pressure testing machine to ensure that the sensor surface is flat and without warping.
[0132] 2. Use a pressure tester to gradually increase the pressure from 0Pa. The maximum test pressure is selected according to the stable performance range of the sensor during the test (for example, 0-200kPa).
[0133] 3. At the same time, the applied pressure and the change in the sensor output signal (resistance) are recorded by the data acquisition system.
[0134] 4. Hold each pressure value for a few seconds to ensure that the sensor output signal is stable before recording.
[0135] 5. Repeat the test at different pressure points (such as 5Pa, 10Pa, 20Pa, etc.) to ensure the reliability and repeatability of the data.
[0136] The test result data table is shown in the following table.
[0137] Table 2 Performance test results of embodiments and comparative examples
[0138]
[0139] The flexible piezoresistive sensor prepared in Example 1 is as follows: Figure 3 As shown in the figure, the schematic diagram of the cyclic electrical signal response under different pressing degrees is as follows Figure 4 As shown, during 1.5s-7.5s, the flexible piezoresistive sensor is in a hard pressing state, and during 9s-15s, the flexible piezoresistive sensor is in a light pinching state.
[0140] As can be seen from the table above, Example 1 shows excellent sensitivity in the full pressure range of 0-200 kPa due to its optimized multi-walled carbon nanotube loading and highly uniform distribution. In particular, in the low pressure range (0-2.5 kPa), its sensitivity reaches -0.14004 kPa. -1 , far exceeding other examples and comparison examples, verifying its high efficiency in accurately measuring small pressure changes. This performance is achieved through sophisticated material engineering and advanced manufacturing technology, ensuring reliability and stability in a wide range of applications.
[0141] Example 2 attempts to reduce costs by reducing the amount of multi-walled carbon nanotubes, resulting in lower sensitivity than Example 1 in all pressure ranges, especially a significant decrease in performance in the low pressure range. The data of this example emphasizes that while trying to reduce costs, performance may be negatively affected. Example 3 improves sensitivity in the low pressure range by improving solvents and electrospinning technology and increasing the amount of multi-walled carbon nanotubes, but its performance in the medium to high pressure range still does not reach the level of Example 1, which shows that although the goal is to increase sensitivity in a specific range, performance in the medium to high pressure range needs to be optimized. Even local optimization needs to maintain attention to the full range of performance.
[0142] The PDMS film thickness of Comparative Example 5 is 20 μm, which is thinner than that of Example 1. Because a smaller material thickness allows for faster deformation, this thinner film design is intended to improve the sensitivity of the film, especially in the low pressure range. However, the results show that the performance is inferior to or close to that of Example 1 in all pressure ranges, because the thinner film cannot disperse the stress well to increase the conductive path, resulting in reduced sensitivity.
[0143] The thickness of the PDMS membrane layer in Comparative Example 6 reaches 1500 μm, which greatly enhances the stability of the structure, but at the same time is likely to limit the sensitivity, especially in applications that require rapid response to small pressure changes. This design choice may make the membrane more stable in the high pressure range, but the sensitivity and response speed in the low pressure range are much lower than those of Example 1.
[0144] Comparative Example 7 describes a MWCNTs composite membrane with a crack-free structure. The crack structure is designed to enhance the flexibility of the membrane and its responsiveness to different pressure changes. It can provide more deformation space at the microscopic level, allowing the membrane to distribute stress more effectively under pressure, and theoretically improve its sensitivity in all pressure ranges. Similar to the theoretical inference, the results show that the sensitivity of the crack-free structure in all ranges is inferior to that of Example 1 with a microcrack structure.
[0145] The MWCNTs composite membrane of Comparative Example 8 has a very thin thickness (0.2 μm) and a small crack spacing (78 μm). Although this ultra-thin film layer may help improve flexibility and fit, its sensitivity in the low pressure range is significantly reduced, mainly because the ultra-thin multi-walled carbon nanotube layer makes the tunneling resistance change very small. In the medium to high pressure range, this design leads to rapid membrane loss and performance degradation.
[0146] The MWCNTs composite film of Comparative Example 9 has a thickness of 10.5 μm and a crack spacing of 122 μm. This thicker film layer helps improve the overall durability and conductivity of the film. This structure may provide better force transmission and distribution, thereby improving sensitivity. However, the results show that the larger multi-walled carbon nanotube thickness and crack spacing in the medium and high pressure range limit its sensitivity, because the larger thickness and gap require a larger pressure deformation to achieve an effective conductivity path connection.
[0147] Combined with reference Figure 7 A smart glove includes a glove body and a flexible piezoresistive sensor, wherein the flexible piezoresistive sensor is attached to the glove body.
[0148] In order to facilitate signal transmission and conversion of the smart gloves, the smart gloves also include a main control board, which includes a fixed resistor, a single-chip microcomputer, a filter, an operational amplifier and a wireless communication module.
[0149] There are four flexible piezoresistive sensors, which are respectively attached to the glove body at the positions of the fingertips of human fingers except the thumb, and are used to identify and collect finger pressure signals; the flexible piezoresistive sensor has a resistor; each of the flexible piezoresistive sensors is connected in series with the fixed resistor to form a voltage divider circuit, which converts the change in resistance value into a change in voltage divider, and then passes through the filter and the operational amplifier in sequence to form a stable voltage signal, which is input into the single-chip microcomputer; the single-chip microcomputer is connected to the wireless communication module; the flexible piezoresistive sensor is the flexible piezoresistive sensor as described above.
[0150] The processed voltage signal is then fed into the microcontroller, which can convert the analog signal into a digital signal through its ADC interface. The microcontroller then analyzes these digital signals using a preset gesture recognition algorithm and finally outputs a signal representing a specific gesture.
[0151] The wireless communication module allows the main control board to connect wirelessly with the Raspberry Pi on the drone. The MCU can initialize the serial port through the UART library, and then the wireless communication module is connected to the MCU through the serial port to wirelessly transmit the gesture signal to the Raspberry Pi on the drone for further processing and response.
[0152] Among them, the connecting circuits between the fixed resistor, single-chip microcomputer, operational amplifier, filter, wireless communication module and flexible piezoresistive sensor are all integrated on the main control board; the main control board integrates the single-chip microcomputer, voltage divider circuit, filter circuit, power supply circuit and wireless communication module, etc. Its power supply circuit can be battery-powered, supporting both USB and embedded battery power supply modes.
[0153] The operational amplifier is located between the filter and the microcontroller, and performs impedance isolation on the signal transmitted from the filter, and then transmits it to the ADC pin of the microcontroller, so that the subsequent circuit will not affect the output of the previous signal source, while keeping the voltage value of the signal unchanged, ensuring the stability of the signal and preventing signal distortion and loss; the operational amplifier model can be TLV9064.
[0154] The output voltage range of the voltage divider circuit is calculated by the following formula:
[0155]
[0156] Among them, V out is the output voltage, V in is the power supply voltage, R1 is a fixed resistor, R S The resistance of the flexible piezoresistive sensor changes. When the flexible piezoresistive sensor is pressed, the resistance changes, and a corresponding voltage value can be generated.
[0157] The flexible piezoresistive sensor can be pressed by pressing the fingertips of the glove body corresponding to the fingers of the human body except the thumb with the thumb. By pressing with different forces, the flexible piezoresistive sensor will transmit different voltage signals, thereby performing intelligent control.
[0158] In a specific embodiment, the circuit schematic diagram of the smart gloves when used is shown in the attached figure. Figure 8 , power supply voltage V in The resistance R of the flexible piezoresistive sensor s , through the voltage divider circuit formed by the fixed resistor R1, it enters the filter C1, then enters the microcontroller D1 through the operational amplifier T1, and then enters the wireless communication module.
[0159] Combined with reference Figure 3 , a drone gesture control method, comprising the following steps:
[0160] Step 1: Put on the smart gloves on your hands and install the drone command execution module on the drone body;
[0161] The drone command execution module includes a flight control module and a Raspberry Pi;
[0162] The Raspberry Pi receives the command signal and converts the command signal into a control signal corresponding to the flight mode of the drone. At the same time, the Raspberry Pi is connected to the flight control module, and the flight control module controls the drone body to complete various actions;
[0163] Step 2: determining whether the flexible piezoresistive sensor is in a hard pressing state or a light pinching state by setting a threshold;
[0164] Step 3: Input the state information combination of the flexible piezoresistive sensor into the single chip microcomputer to obtain the gesture state corresponding to each combination of information and the instruction corresponding to the gesture state;
[0165] Step 4: The executor performs corresponding gestures with fingers as required, and the single chip microcomputer transmits the command signal to the Raspberry Pi through the wireless communication module;
[0166] Step 5: After receiving the command signal, the Raspberry Pi converts the gesture into a drone control signal, thereby controlling the drone to complete the command action.
[0167] After receiving the command signal, the Raspberry Pi can convert the gesture action signal into a drone control signal through Dronekit to control the flight action of the drone.
[0168] The smart gloves are the above-mentioned smart gloves.
[0169] Among them, the Raspberry Pi has a wireless communication receiving module inside, which can receive signals; the Raspberry Pi also converts the signals.
[0170] Combined with reference Fig. 9 The drone gesture control method of the present application, after assembling the smart gloves and the drone hardware, performs gesture actions, and the smart gloves can collect the signals transmitted by the gesture actions; the single-chip microcomputer converts the signals and sends specific gesture signals; the drone Raspberry Pi can receive the gesture signals and convert them into corresponding signals in the flight control module; finally, the drone movement is controlled through the flight control module.
[0171] The present application provides a drone gesture control method that is paired with the above-mentioned smart gloves, so that the operator only needs to press the flexible piezoresistive sensor on the glove body to directly control the drone to complete the command action. The operation method is simple, intuitive, and easy to learn, which reduces the technical threshold of the operator; the gesture control method allows the operator to control through natural hand movements, which not only makes the operation more intuitive, but also helps the operator maintain comprehensive monitoring of the surrounding environment, thereby improving the safety and efficiency of the interaction.
[0172] At the same time, smart gloves can also be used in harsh environments, can accurately identify gesture changes, and improve the accuracy of drone control. The environment does not affect its sensitivity and accuracy or has little impact on its sensitivity and accuracy, which makes smart gloves less limited and has a wider range of application scenarios.
[0173] Gestures and their corresponding instructions can be set according to actual needs, thus providing operators with a personalized and adaptable interaction solution.
[0174] To this end, the present application provides preferred gesture states in step three and instructions corresponding to the gesture states, as follows.
[0175] The gesture state in step 3 and the instruction corresponding to the gesture state include:
[0176] The thumb gently pinches the index finger, and the drone performs a descent operation;
[0177] Press the thumb hard on the index finger, and the drone will land.
[0178] Squeeze the middle finger with your thumb, and the drone will move forward.
[0179] Press the middle finger with your thumb to make the drone move backwards.
[0180] Slightly pinch the ring finger with the thumb, and the drone will fly to the left;
[0181] Press the ring finger hard with the thumb, and the drone will fly to the right;
[0182] Squeeze the little finger with your thumb, and the drone will ascend.
[0183] Press the little finger hard with the thumb, and the drone will take off;
[0184] The light pinching pressure is 5-30 kPa, and the heavy pressing pressure is 80-200 kPa.
[0185] The drone gesture control method used with the above-mentioned smart gloves relies on gesture changes to control the drone, which can quickly and accurately reflect the operator's actual operating intentions, making the control of the drone more sensitive and precise; and can provide the operator with a personalized and adaptable interaction solution by inputting and modifying gesture commands, thereby improving the operator's user experience.
[0186] In summary, in the flexible piezoresistive sensor, smart gloves and drone gesture control method of the present invention, the flexible piezoresistive sensor can quickly change its resistance value when subjected to force, thereby achieving fast response and high-sensitivity pressure detection. It has high sensitivity and accuracy, can accurately capture and transmit tiny pressure changes, and can be applied to smart gloves using the drone gesture control method. It can sensitively sense the pressure changes brought about by gesture changes, thereby accurately controlling the drone.
[0187] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A flexible piezoresistive sensor, characterized in that: It includes a micro-conical polydimethylsiloxane film layer, a composite film layer and a polydimethylsiloxane film layer stacked in sequence from bottom to top; The composite film layer comprises a thermoplastic polyurethane elastomer fiber film and a microcrack multi-walled carbon nanotube film, the thermoplastic polyurethane elastomer fiber film is bonded to the microconical polydimethylsiloxane film layer, and the microcrack multi-walled carbon nanotube film is bonded to the polydimethylsiloxane film layer; both ends of the microcrack multi-walled carbon nanotube film are attached with conductive electrode materials; The preparation steps of the composite film layer include: coating an aqueous dispersion of multi-walled carbon nanotubes on a thermoplastic polyurethane elastomer fiber film, drying, and then stretching and rebounding to obtain the composite film layer having a micro-crack multi-walled carbon nanotube film; the thickness of the micro-crack multi-walled carbon nanotube film is 1-10 μm; The preparation steps of the micro-cone polydimethylsiloxane film layer include: uniformly mixing a polydimethylsiloxane matrix and a curing agent, pouring the mixture into a mold with a micro-cone structure, curing the mixture, and then taking out the micro-cone polydimethylsiloxane film layer to obtain the micro-cone polydimethylsiloxane film layer; the thickness of the micro-cone polydimethylsiloxane film layer is 0.2-1 mm.
2. The flexible piezoresistive sensor according to claim 1, characterized in that: The thickness ratio of the micro-cone polydimethylsiloxane film layer, the micro-crack multi-walled carbon nanotube film, the thermoplastic polyurethane elastomer fiber film and the polydimethylsiloxane film layer is: (200-1000): (1-10): (50-200): (200-1000).
3. The flexible piezoresistive sensor according to claim 1, characterized in that: The preparation steps of the thermoplastic polyurethane elastomer fiber membrane include: dissolving a thermoplastic polyurethane elastomer in an organic mixed solvent to obtain a thermoplastic polyurethane elastomer solution, and subjecting the thermoplastic polyurethane elastomer solution to electrospinning to obtain the thermoplastic polyurethane elastomer fiber membrane; The organic mixed solution is selected from at least one of a mixed solution of dimethylformamide and ethyl acetate and a mixed solution of dimethylformamide and tetrahydrofuran; In the thermoplastic polyurethane elastomer solution, the mass fraction of the thermoplastic polyurethane elastomer is 18-25wt%; The parameters of the electrospinning treatment are: voltage 14-16 kV, distance between the needle and the collector 12-18 cm, and flow rate of the thermoplastic polyurethane elastomer solution 1-4 mL / h.
4. The flexible piezoresistive sensor according to claim 1, characterized in that: In the step of preparing the composite film layer, the aqueous dispersion of multi-walled carbon nanotubes contains multi-walled carbon nanotubes and a dispersant, the mass fraction of the multi-walled carbon nanotubes is 8-12wt%, and the mass fraction of the dispersant is 1-4wt%; The multi-walled carbon nanotubes have a diameter of 10-25 nm and a length of 5-15 μm; The crack spacing of the micro-cracked multi-walled carbon nanotube film is 80-120 μm.
5. The flexible piezoresistive sensor according to claim 1, characterized in that: In the step of preparing the micro-conical polydimethylsiloxane film layer, the mass ratio of the polydimethylsiloxane matrix to the curing agent is (8-12):
1.
6. The flexible piezoresistive sensor according to claim 1, characterized in that: The flexible piezoresistive sensor also includes a first polyurethane film layer and a second polyurethane film layer, wherein the first polyurethane film layer is arranged below the micro-conical polydimethylsiloxane film layer, and the second polyurethane film layer is arranged above the polydimethylsiloxane film layer; the thickness of the first polyurethane film layer is 50-150 μm, and the thickness of the second polyurethane film layer is 50-150 μm.
7. A smart glove, characterized in that: It comprises a glove body and a flexible piezoresistive sensor according to any one of claims 1 to 6; the flexible piezoresistive sensor is attached to the glove body.
8. The smart glove according to claim 7, characterized in that: The smart glove also includes a main control board, which includes a fixed resistor, a single-chip microcomputer, a filter, an operational amplifier and a wireless communication module; there are four flexible piezoresistive sensors, which are respectively attached to the glove body at the positions of the fingertips of the human fingers except the thumb, and are used to identify and collect finger pressure signals; the single-chip microcomputer is connected to the wireless communication module; The flexible piezoresistive sensor has a resistor; each of the flexible piezoresistive sensors is connected in series with the fixed resistor to form a voltage divider circuit, converting the change in resistance value into a voltage divider change, which then passes through the filter and the operational amplifier in sequence to form a stable voltage signal, which is input into the single-chip microcomputer.
9. A drone gesture control method, characterized in that: The following steps are involved: Step 1: Put on the smart gloves on your hands and install the drone command execution module on the drone body; The smart glove is the smart glove according to claim 8; The drone command execution module includes a flight control module and a Raspberry Pi; The Raspberry Pi receives the command signal and converts the command signal into a control signal corresponding to the flight mode of the drone; at the same time, the Raspberry Pi is connected to the flight control module, and the flight control module controls the drone body to complete various actions; Step 2: determining whether the flexible piezoresistive sensor is in a hard pressing state or a light pinching state by setting a threshold; Step 3: Input the state information combination of the flexible piezoresistive sensor into the single chip microcomputer to obtain the gesture state corresponding to each combination of information and the instruction corresponding to the gesture state; Step 4: The executor performs corresponding gestures with fingers as required, and the single chip microcomputer transmits the command signal to the Raspberry Pi through the wireless communication module; Step 5: After receiving the command signal, the Raspberry Pi converts the gesture into a drone control signal, thereby controlling the drone to complete the command action.
10. The drone gesture control method according to claim 9, characterized in that: The gesture state in step 3 and the instruction corresponding to the gesture state include: The thumb gently pinches the index finger, and the drone performs a descent operation; Press the thumb hard on the index finger, and the drone will land. Squeeze the middle finger with your thumb, and the drone will move forward. Press the middle finger with your thumb to make the drone move backwards. Slightly pinch the ring finger with the thumb, and the drone will fly to the left; Press the ring finger hard with the thumb, and the drone will fly to the right; Squeeze the little finger with your thumb, and the drone will ascend. Press the little finger hard with the thumb, and the drone will take off; The light pinching pressure is 5-30 kPa, and the heavy pressing pressure is 80-200 kPa.
Citation Information
Patent Citations
Strain sensitive material for electronic skin and preparation method thereof
CN108981986A
Composite film flexible pressure sensor doped with isopropanol and preparation method thereof
CN114964575A
Gradient multilayer flexible piezoresistive sensor and preparation method thereof
CN115931186A
Microcrack strain sensor and preparation method therefor
WO2023220986A1